Assessment of cement-based boards reinforced with fibers extracted from Andean Ichu grass (SCIÉNDO INGENIUM, 2025)
The continuous growing of the construction industry it is challenging to find the right choice for raw materials especially fibers for cement-based composites. In this study, raw Ichu fibers were evaluated to be used as reinforcement of cement matrices; mercerization treatment of the original fibers followed by the shear defibrillation technique were used to obtain the pulp; afterward, slurry-dewatering with the final pressing process technique were used to manufacture the composites boards. Results show that Ichu fibers required low aggressive mercerization treatment; furthermore, with mechanical shear defibrillation more than 80% of the defibrillated fiber present an aspect ratio over 80. The manufactured fiber cement composites board present a modulus of rupture over 8 MPa; moreover, with outdoor and indoor aging, samples modulus of rupture increases, reaching around 13.5 MPa for the outdoor aging; furthermore, progressive embrittlement was observed with impact over aging time. Finally, based on the mechanical properties of the boards, results suggest that with 9%wt of the Ichu pulp fibers as reinforcement, boards shown a bests characteristic.
Keywords: Ichu fibers; fiber cement composites; natural fibers; mechanical properties; physical properties